A cross-sectional prospective study on the relationship between serum liver enzymes and hypertension in patients accessing health care services at Nebbi General Hospital, Nebbi District. - Oyungrwoth , Edimond; Salamu , Geofrey Akiiki; Akullo , Mirriam; Mabonga, Habert; Oromcan , Benjamin Wathum (Student’s Journal of Health Research Africa, 2026)
Background Hypertension is associated with cardiovascular disease (CVD) and has a relationship to liver health. The objective of the study was to establish the relationship between serum liver enzymes and hypertension among patients accessing health care services at Nebbi General Hospital. Method A cross-sectional prospective study was carried out to evaluate the relationship between liver enzymes and hypertension in Nebbi general hospital between December 2022 and May 2023. Data was collected by performing laboratory analysis of liver enzymes and interviewing the patient about their biodata. The data was sorted and analyzed using SPSS for Windows version 25. The data analyzed was presented by using charts, figures, tables, graphs, and useful conclusions were made. Results The study analyzed data from 108 individuals and observed varying prevalence rates of elevated liver enzymes, ranging from 0.9% to 46.3%, based on different liver enzymes (ALP 0.9%, ALT 7.4%, AST 27.8%, and GGT 46.3%). The analysis of the data further revealed that all liver enzymes, except ALT, were elevated in females (P>0.05). Additionally, certain liver enzymes, such as ALT and ALP, were elevated in the age group 50-59 years, while AST and GGT were elevated in the age group of 60-69 years (P>0.05). Conclusions The current research findings align with previous studies indicating a relationship between elevated liver enzymes and hypertension. This current study suggests a potential link between hypertension and liver dysfunction, as indicated by elevated liver enzymes. Recommendations The study underscores the importance of monitoring liver health in individuals with hypertension and raises awareness of potential liver-related complications. Further research is needed to elucidate the underlying mechanisms and clarify the clinical implications of these associations.